2009
DOI: 10.1063/1.3066906
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy and ultraviolet photoelectron spectroscopy investigation of Al-related dipole at the HfO2/Si interface

Abstract: The presence of an ultrathin oxide layer at the high-k/SiO2 interface may result in an interfacial dipole related to the specific high-k dielectric used for the gate stacks. 1 nm HfO2/x nmAl2O3/SiO2/Si stacks with different x values (x=0, 0.4, 0.8, 1.2) have been prepared by atomic layer deposition. Using photoelectron spectroscopy, an Al-related interfacial dipole in the HfO2/Al2O3/SiO2 gate stack has been identified. X-ray photoelectron spectroscopy analysis shows that the dipole is correlated with the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…Recently, there are increased interests on the physical insight of the dipole layer formation by X-ray photoelectron spectroscopy (XPS) [353,[372][373][374][375][376]. The direct evidence of the dipole effects in high-k stacks is expected to be obtained.…”
Section: Work Function Tuning By Interfacial Dipole In High-k Gate Stmentioning
confidence: 99%
“…Recently, there are increased interests on the physical insight of the dipole layer formation by X-ray photoelectron spectroscopy (XPS) [353,[372][373][374][375][376]. The direct evidence of the dipole effects in high-k stacks is expected to be obtained.…”
Section: Work Function Tuning By Interfacial Dipole In High-k Gate Stmentioning
confidence: 99%
“…It was shown that the position of the capping layers' atoms is important for their functionality, 19,20 and particularly it was shown with different configurations that the contact of Al oxide with SiO 2 is responsible for the EWF increase. 12,21,22 These effects have been further utilized recently for improving metal-semiconductor contacts. 23,24 In a recent study, 22 we have shown that the formation of a Ta suboxide layer formed at a Ta-Al 2 O 3 interface resulted in an EWF increase of 0.4 eV.…”
Section: Introductionmentioning
confidence: 98%
“…7,[9][10][11]14,15 Narayanan et al reviewed the construction of high-κ gate nFETs and pFETs, discussing the inclusion of capping layers as an important means of controlling the threshold voltage, 14 while Bosman et al recently studied the distribution of chemical elements within a HfO 2 /SiO 2 gate stack from Al and La capping layers. 7 When these studies are coupled with the measurements of the valence band offset (VBO), 11 it shows that Al tends to decrease the VBO of HfO 2 /SiO 2 , while La increases it, but without any clear explanation of the intrinsic cause.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of dopants have recently been studied both theoretically and experimentally, including Al, [7][8][9][10][11][12][13] La,7,[10][11][12][13][14] Mg, 14,15 and Sr. 10 Of particular interest here are the dopants introduced through diffusion from capping layers of La, Al, or Mg containing materials. 7,[9][10][11]14,15 Narayanan et al reviewed the construction of high-κ gate nFETs and pFETs, discussing the inclusion of capping layers as an important means of controlling the threshold voltage, 14 while Bosman et al recently studied the distribution of chemical elements within a HfO 2 /SiO 2 gate stack from Al and La capping layers.…”
Section: Introductionmentioning
confidence: 99%